2018
DOI: 10.1111/his.13735
|View full text |Cite
|
Sign up to set email alerts
|

Grading of renal cell carcinoma

Abstract: Grading of renal cell carcinoma (RCC) has been recognised as a prognostic factor for almost 100 years. Numerous grading systems have been proposed, initially focusing upon a constellation of cytological features and more recently on nuclear morphology. It has been recommended that grading of RCC should be based upon nucleolar prominence/eosinophilia for grades 1–3, while grade 4 requires nuclear anaplasia (including tumour giant cells, sarcomatoid differentiation and/or rhabdoid morphology). The grading system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
160
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(165 citation statements)
references
References 83 publications
(160 reference statements)
2
160
0
3
Order By: Relevance
“…RCC with sarcomatoid differentiation is classified as grade 4 by the WHO/ISUP grading system [11]. However, grade 4 RCC with sarcomatoid differentiation has significantly worse CSS than grade 4 RCC without differentiation [10,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RCC with sarcomatoid differentiation is classified as grade 4 by the WHO/ISUP grading system [11]. However, grade 4 RCC with sarcomatoid differentiation has significantly worse CSS than grade 4 RCC without differentiation [10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Gökden et al [9] reported an incidence of rhabdoid differentiation of 4.7% and revealed associations between rhabdoid differentiation and increased grade and stage for the first time. Delahunt et al [11] reviewed previous studies that reported survivals ranging from 8 to 31 months. In a more recent study of grade 4 RCC, 45 [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…76 The World Health Organization/International Society of Urologic Pathology nucleolar grade is now used in place of the Fuhrman nuclear grade. 1,19,77,78 This grading system is based on nucleolar prominence for grades 1 through 3, whereas grade 4 consists of more aggressive rhabdoid, sarcomatoid, and anaplastic morphologies. 1,19,77,78 The World Health Organization/International Society of Urologic Pathology nucleolar grade correlates with prognosis in both clear cell and papillary renal cell carcinoma, but not with chromophobe renal cell carcinoma, and the latter should not be graded.…”
Section: Updates In Kidney Cancer Stagingmentioning
confidence: 99%
“…However, its clinical significance could not be demonstrated for chRCC, because prominent nucleoli are not frequent in chRCC. Therefore, it was recommended that chRCC should not be graded [2,[7][8][9].…”
mentioning
confidence: 99%